The impact of living with home enteral feeding: perspectives of people who have had a diagnosis of head and neck cancer. Issue 5 (15th July 2019) - Thomas, A.; Sowerbutts, A. M.; Burden, S. T.
Abstract: Background: The number of people with head and neck cancer who are home enterally fed continues to grow each year. Insertion of a feeding tube is common place in these patients and is considered to have a detrimental effect on quality of life. The present study aimed to investigate the daily impact of home enteral feeding (HEF) from the perspective of people who have had a diagnosis of head and neck cancer. Methods: The methodology aligned with interpretative phenomenology analysis. People who were home enterally fed, with head and neck cancer, and aged ≥18 years were recruited. Data were collected using semi‐structured interviews and analysis focused on what the daily impact of HEF meant for participants. Results: Data saturation was achieved after interviewing 15 participants. Five cluster themes were identified. 'Deviation from the norm' encompassed change and loss of normality. 'Regaining control leading to empowerment' encompassed participant empowerment through development of new skills and adjusting the feeding regime. 'Creating a new normal' involved making adjustments to facilitate inclusion and participation. 'External modifiers of the HEF experience' and 'internal modifiers of the HEF experience' encompassed the identification of external and internal HEF factors that influenced HEF adaptation. Conclusions: HEF was found to influence peoples' daily lives substantially and required extensive adjustments for individuals to find a new normal. A greater level of interpretation was provided beyond the current evidence‐base for this group. Policymakers and clinicians should recognise the wider impact of HEF and ensure that this awareness is embedded in clinical practice.